1939
DOI: 10.2134/agronj1939.00021962003100090005x
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Measure of Kernel Hardness in Wheat1

Abstract: ANY simple test that will aid the wheat breeder in measuring 1"\. characteristics of grain is of value in increasing the efficiency of the breeding program. In the eastern soft wheat region hard wheats are being used extensively as parents to secure resistance to various diseases and a simple test is especially needed for identifying, in the early generations, hybrid lines with soft grain. Hard wheats in general produce coarse granular flour and soft wheats fine smooth flour. The particle size index test devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1948
1948
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…H. H. KRAMER AND H. R. ALBRECHT 2 T HE barley pearler has come into prominance as a measure of kernel hardness in wheat since its use for that purpose was first proposed by Taylor, Bayles, and Fifield (4) 3 in 1939. They showed that the pearling index is closely correlated with the particle size index developed by Cutler and Brinson (r), and found fair agreement between the pearling index and the fermentation time test suggested by Cutler and Worzella (2).…”
mentioning
confidence: 99%
“…H. H. KRAMER AND H. R. ALBRECHT 2 T HE barley pearler has come into prominance as a measure of kernel hardness in wheat since its use for that purpose was first proposed by Taylor, Bayles, and Fifield (4) 3 in 1939. They showed that the pearling index is closely correlated with the particle size index developed by Cutler and Brinson (r), and found fair agreement between the pearling index and the fermentation time test suggested by Cutler and Worzella (2).…”
mentioning
confidence: 99%
“…Hardness values obtained by BP were expressed as ARI instead of pearling index (PI). PI was defined by Taylor et al (1939) and calculated as percent of surface removal (or % of wheat pearled off). By definition, the two units are convertible based on the formula, ARI = 100 -PI.…”
Section: Hardness Measurement By Bpmentioning
confidence: 99%
“…NIR hardness score was calibrated by the same reference material. For hardness values obtained by BP and other abrasive-action-based equipment (such as TADD), several expressions were used including 1) pearling index (PI) or % of kernel weight pearled off (Taylor et al 1939); 2) pearling resistance index (PRI), defined as the weight of pearled grains (Obuchowski and Bushuk 1980); 3) rate constant, defined as % milling loss/min (Lawton and Faubion 1989); and 4) abrasive hardness index (AHI), defined as time (sec) required to pearl 1% off (Reichert et al 1981). In this study, hardness values measured by SS and BP are expressed as % of remaining kernel weight after a given time of abrading and defined as abrasion resistance index (ARI).…”
Section: Expression Of Hardnessmentioning
confidence: 99%
See 1 more Smart Citation
“…The pearling test, originated by Taylor, Bayles, and Fifield (12) measures the kernel hardness of wheat by subjecting the grain to the abrasive action of a revolving stone in a commercial barley pearler. High correlations between results of the pearling test and tests measuring gluten strength in soft wheats have been reported by Bayfield et al ( 2, 3), Morris et al (9) and Bowman et al (5).…”
Section: Literature Reviewmentioning
confidence: 99%